2020
DOI: 10.1186/s13023-020-01572-9
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genetic spectrum of isolated macrodactyly: somatic mosaicism of PIK3CA and AKT1 oncogenic variants

Abstract: Background Isolated macrodactyly is a severe congenital hand anomaly with functional and physiological impact. Known causative genes include PIK3CA, AKT1 and PTEN. The aim of this study is to gain insights into the genetics basis of isolated macrodactyly. Results We enrolled 24 patients with isolated macrodactyly. Four of them were diagnosed with Proteus syndrome based on skin presentations characteristic to this disease. Targeted next-generation sequencing was performed using patients’ blood and affected ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Most of these disorganized overgrowths of essentially mesenchymal elements have been more recently termed PTEN hamartoma of soft tissue (PHOST) [178]. In rare cases of Cowden and Cowdenlike syndromes as well as in proteus syndrome, other susceptibility genes have been reported (see below) [179][180][181][182].…”
Section: Pten Hamartoma Tumor Syndromes (Pths)mentioning
confidence: 99%
“…Most of these disorganized overgrowths of essentially mesenchymal elements have been more recently termed PTEN hamartoma of soft tissue (PHOST) [178]. In rare cases of Cowden and Cowdenlike syndromes as well as in proteus syndrome, other susceptibility genes have been reported (see below) [179][180][181][182].…”
Section: Pten Hamartoma Tumor Syndromes (Pths)mentioning
confidence: 99%
“…5 The aetiology of macrodactyly is not well understood, however, its association with PIK3CA /AKT1 genes has been reported in 24 patients mosaic for this variant. 6,7 In this case study, we reported a rare congenital macrodactyly of second and third toe of right foot along with deformed leg in 16-year-old girl.…”
Section: Introductionmentioning
confidence: 81%
“…We included ten families diagnosed with CCA and carrying pathogenic FBN2 variant from Beijing Jishuitan Hospital and Peking Union Medical College Hospital based on the D eciphering disorders I nvolving S coliosis and CO morbidities (DISCO) study ( http://www.discostudy.org/ ) ( Tian et al, 2020 ; Sun et al, 2021 ). Informed consent was obtained from all patients or their guardians.…”
Section: Methodsmentioning
confidence: 99%